Spatio-temporal distribution of temperature, salinity and suspended sediment on the deltaic front of the Magdalena River: Influence on nutrient concentration and primary productivity (2020)
The characteristics of estuaries depend mainly on the magnitude and variability of river discharge and tidal forcing (Kjerfve, 1994). Estuaries present strong temporal and spatial gradients with respect to their physical, chemical and biological properties, as a result of changes in fluvial contributions (Nogueira et al., 1997). Therefore, biogeochemical processes are extremely complex (Fourqurean et al., 1993; Fernández-Nóvoa et al., 2015). Temperature and salinity are the most relevant features of coastal marine ecosystem dynamics (Urquhart et al., 2013), as variations in these parameters can influence the movement of water masses, water column stratification caused by density differences, transport of sediments, and mixing conditions (Bianchi, 2007; Geyer, 2010; Obeso-Nieblas et al., 2012; Osadchiev et al., 2017). Also, temperature and salinity may play roles in nutrient distributions and concentrations (Windom et al., 2006), and biogeochemical processes and ecological productivity, through alterations in biochemical reactions that regulate the enzymatic processes of respiration and photosynthesis (Xia and Jiang, 2015; Quamrul et al., 2016). The physical dynamics of estuaries/deltas of the micro-tidal domain, which are highly stratified and turbid, have been little studied. Therefore, we lack detailed knowledge regarding relationships among spatio-temporal variations in salinity and temperature, the extent and structure of convergence fronts and the mixed layer, nutrient distribution and primary productivity in this type of estuary.